Giving Critical Context to the Deportee Phenomenon - Headley, Bernard (Social justice, 2006)
Part of a special issue on immigration rights and national insecurity. The deportation of people from Britain, Canada, and especially the U.S. to Jamaica and other Caribbean countries has been blamed for soaring crime rates in the region. In fact, most deportees are returned for nominal infractions of America's Illegal Immigration Reform and Immigrant Responsibility Act of 1996; also among their numbers are expelled undocumented workers and visa overstayers, nonreporting green card holders and out-of-status students, apprehended stowaways, and rejected asylum seekers. Such deportations are more about enforcing the sanctions of the legislation and freeing up prison space than about serious criminality among the deportees.